Madrasah Principal Management in Improving the Quality of Research Madrasahs - Rosalia Sari; Murniati Murniati; Bahrun Bahrun (STAI Hubbulwathan Duri, 2023)
The research objectives are to (1) describe the planning of the research madrasah quality improvement program. (2) Describe the organization of the research madrasah program. (3) Describe the implementation of the research madrasah program. (4) Describe the supervision of the research madrasah program. The method used is the descriptive qualitative method. Data collection techniques through observation, interviews, and documentation studies. The research subjects were: the head of the madrasah, the deputy head, the research madrasah quality development team, supervisors, committees, teachers and accompanying teachers. Data analysis techniques through data reduction, data presentation, and drawing conclusions. The results showed: (1) Program planning was carried out at the beginning of the year through a working meeting with the madrasah head, deputy head, supervising teachers, supervisors and committees, the formation of a research class, the establishment of a curriculum, the preparation of a research madrasah program work plan. (2) Organizing is done by assigning tasks to teachers who have competence in the field of research, the establishing a research madrasah implementing structure, and the establishing of a quality development unit. (3) Carrying out according to schedule, the research carried out aims to grow students' knowledge, develop a culture of literacy, writing and has participated in several competitions held, such as the MYRES, KOPSI, LIPI, KTI MTs Istiqlal and Robotics events. (4) Supervision has not been carried out properly. This is because there is no special team that has the task as a unit to carry out supervision, and also there is no supervision schedule. The conclusions showed the implementation of this research madrasah quality improvement program is due to program implementation regulations, the commitment of the madrasah principal, the magnitude of student interest, the availability of facilities and infrastructure and the budget for program implementation.